الشرح الموضوعي للحديث الشريف : دراسة نظرية تطبيقية - اشرفي، هيفاء عبد العزيز،‏ ‏1969- (al-Jami'ah al-Islamiyah al-'Alamiyah bi-Maliziya, 2007)
This work is devoted to the issue of Thematic Interpretation of Hadith as a mean of interaction between Hadith and different issues of life. The study aims at bringing to light this type of interpretation; theoretically, and practically in a way which suits the needs of recent days. The work highlights this manner of interpretation by presenting its definition, significance and historical background, from the birth of Islam until present era. It points out the three types of thematic interpretation and identifies their various steps and principles. To enhance the theoretical side; practical examples for the three types of thematic interpretation were introduced. The study utilized the historical method to trace the origins, and growth of Hadith interpretations. The inductive method was used to extract the Hadith narations related to the topics which were chosen for the examples of this study. While the analytical method was concerned to examine issues in the light of hadith, in order to realize Its views regarding them. The thesis shows the significance of relying on the theoretical part to accomplish a comprehensive thematic interpretation; which confirms that Islam is strongly related to all aspects of life, and not a mere religion for individual ritualistic manifestation.